APLIKASI TEPUNG CANGKANG TELUR AYAM TERHADAP PERTUMBUHAN BENIH KOPI ROBUSTA (Coffea canephora L.) PADA MEDIA GAMBUT - Rosmalinda, Rosmalinda; Setiawan, Beny; Lita, Apriani (Politeknik Negeri Ketapang, 2022)
Robusta (Coffea canephora L.) is one type of plantation plant that has been cultivated for a long time and has a fairly high economic value. Egg shell contains 97% calcium carbonate, phosphorus, magnesium, sodium and potassium. This study aims to determine the effect of giving egg shell flour on the growth of coffee seedlings on peat media. This research was conducted using a completely randomized design (CRD) consisting of 5 treatments. The treatments were K0: egg shell 0 g polybag-1; K1: 6,25 g polybag-1; K2: 10 g polybag-1; K3: 13, 75 g polybag-1; and K4: 17,50 g polybag-1. Each treatment was repeated 6 times, each replication consisted of 3 plant samples until there were 90 experimental units. The data that has been obtained were analyzed using Analysis of Variance (ANOVA). Data that has a significant effect, continued with the Duncan Multiple Range Test (DMRT) at a level of 5%. The provision of egg shell had an effect on the growth of plant height, number of leaves, stem diameter, root length and dry weight of robusta plants. Egg shell at a dose of 17,50 g polybag-1 was the best dose that affected the vegetative growth of coffee.